We will learn how to prove the property of the inverse trigonometric function, 2 arctan(x) = arctan(\(\frac{2x}{1 - x^{2}}\)) = arcsin(\(\frac{2x}{1 + x^{2}}\)) = arccos(\(\frac{1 - x^{2}}{1 + x^{2}}\))
or, 2 tan\(^{-1}\) x = tan\(^{-1}\) (\(\frac{2x}{1 - x^{2}}\)) = sin\(^{-1}\) (\(\frac{2x}{1 + x^{2}}\)) = cos\(^{-1}\) (\(\frac{1 - x^{2}}{1 + x^{2}}\))
Proof:
Let, tan\(^{-1}\) x = θ
Therefore, tan θ = x
We know that,
tan 2θ = \(\frac{2 tan θ}{1 - tan^{2}θ}\)
tan 2θ = \(\frac{2x}{1 - x^{2}}\)
2θ
= tan\(^{-1}\)(\(\frac{2x}{1 - x^{2}}\))
2 tan\(^{-1}\) x = tan\(^{-1}\)(\(\frac{2x}{1 - x^{2}}\)) …………………….. (i)
Again, sin 2θ = \(\frac{2 tan θ}{1 + tan^{2}θ}\)
sin 2θ = \(\frac{2x}{1 + x^{2}}\)
2θ = sin\(^{-1}\)(\(\frac{2x}{1 + x^{2}}\) )
2 tan\(^{-1}\) x = sin\(^{-1}\)(\(\frac{2x}{1 + x^{2}}\)) …………………….. (ii)
Now, cos 2θ = \(\frac{1 - tan^{2}θ}{1 + tan^{2}θ}\)
cos 2θ = \(\frac{1 - x^{2} }{1 + x^{2} }\)
2θ = cos\(^{-1}\) (\(\frac{1 - x^{2} }{1 + x^{2} }\))
2 tan\(^{-1}\) x = cos (\(\frac{1 - x^{2} }{1 + x^{2} }\)) …………………….. (iii)
Therefore, from (i), (ii) and (iii) we get, 2 tan\(^{-1}\) x = tan\(^{-1}\) \(\frac{2x}{1 - x^{2}}\) = sin\(^{-1}\) \(\frac{2x}{1 + x^{2}}\) = cos\(^{-1}\) \(\frac{1 - x^{2}}{1 + x^{2}}\) Proved.
Solved examples on property of inverse circular function 2 arctan(x) = arctan(\(\frac{2x}{1 - x^{2}}\)) = arcsin(\(\frac{2x}{1 + x^{2}}\)) = arccos(\(\frac{1 - x^{2}}{1 + x^{2}}\)):
1. Find the value of the inverse function tan(2 tan\(^{-1}\) \(\frac{1}{5}\)).
Solution:
tan (2 tan\(^{-1}\) \(\frac{1}{5}\))
= tan (tan\(^{-1}\) \(\frac{2 × \frac{1}{5}}{1 - (\frac{1}{5})^{2}}\)), [Since, we know that, 2 tan\(^{-1}\) x = tan\(^{-1}\)(\(\frac{2x}{1 - x^{2}}\))]
= tan (tan\(^{-1}\) \(\frac{\frac{2}{5}}{1 - \frac{1}{25}}\))
= tan (tan\(^{-1}\) \(\frac{5}{12}\))
= \(\frac{5}{12}\)
2. Prove that, 4 tan\(^{-1}\) \(\frac{1}{5}\) - tan\(^{-1}\) \(\frac{1}{70}\) + tan\(^{-1}\) \(\frac{1}{99}\) = \(\frac{π}{4}\)
Solution:
L. H. S. = 4 tan\(^{-1}\) \(\frac{1}{5}\) - tan\(^{-1}\) \(\frac{1}{70}\) + tan\(^{-1}\) \(\frac{1}{99}\)
= 2(2 tan\(^{-1}\) \(\frac{1}{5}\)) - tan\(^{-1}\) \(\frac{1}{70}\) + tan\(^{-1}\) \(\frac{1}{99}\)
= 2(tan\(^{-1}\) \(\frac{2 × \frac{1}{5}}{1 - (\frac{1}{5})^{2}}\)) - tan\(^{-1}\) \(\frac{1}{70}\) + tan\(^{-1}\) \(\frac{1}{99}\), [Since, 2 tan\(^{-1}\) x = tan\(^{-1}\)(\(\frac{2x}{1 - x^{2}}\))]
= 2 (tan\(^{-1}\) \(\frac{2\frac{1}{5}}{1 - (\frac{1}{25})}\))- tan\(^{-1}\) \(\frac{1}{70}\) + tan\(^{-1}\) \(\frac{1}{99}\),
= 2 tan\(^{-1}\) \(\frac{5}{12}\) - (tan\(^{-1}\) \(\frac{1}{70}\) - tan\(^{-1}\) \(\frac{1}{99}\))
= tan\(^{-1}\) (\(\frac{2 × \frac{5}{12}}{1 - (\frac{5}{12})^{2}}\)) - tan\(^{-1}\) (\(\frac{\frac{1}{70} - \frac{1}{99}}{1 + \frac{1}{77} × \frac{1}{99}}\))
= tan\(^{-1}\) \(\frac{120}{199}\) - tan\(^{-1}\) \(\frac{29}{6931}\)
= tan\(^{-1}\) \(\frac{120}{199}\) - tan\(^{-1}\) \(\frac{1}{239}\)
= tan\(^{-1}\) (\(\frac{\frac{120}{199} - \frac{1}{239}}{1 + \frac{120}{119} × \frac{1}{239}}\))
= tan\(^{-1}\) 1
= tan\(^{-1}\) (tan \(\frac{π}{4}\))
= \(\frac{π}{4}\) = R. H. S. Proved.
● Inverse Trigonometric Functions
11 and 12 Grade Math
From 2 arctan(x) to HOME PAGE
Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.
Sep 15, 24 04:57 PM
Sep 15, 24 04:08 PM
Sep 15, 24 03:16 PM
Sep 14, 24 04:31 PM
Sep 14, 24 03:39 PM
New! Comments
Have your say about what you just read! Leave me a comment in the box below. Ask a Question or Answer a Question.